Isolation and functional analysis of OsAOS1 promoter for resistance to Nilaparvata lugens Stål infestation in rice. Issue 3 (14th December 2021) - Li, Hanpeng; Xu, Xueliang; Han, Kehong; Wang, Zhengjie; Ma, Weihua; Lin, Yongjun; Hua, Hongxia
Abstract: Insect pests have a great impact on the yield and quality of crops. Insecticide applications are an effective method of pest control, however, they also have adverse effects on the environment. Using insect‐inducible promoters to drive insect‐resistant genes in transgenic crops is a potential sustainable pest management strategy, but insect‐inducible promoters have been rarely reported. In this study, we found rice allene oxide synthase gene ( AOS, LOC_Os03g12500) can be highly upregulated following brown planthopper ( Nilaparvata lugens Stål, BPH) infestation. Then, we amplified the promoter of OsAOS1 and the β ‐ glucuronidase reporter gene was used to analyze the expression pattern of the promoter. Through a series of 5ʹ truncated assays, three positive regulatory regions in response to BPH infestation in the promoter were identified. The transgenic plants, P1R123‐min 35S and P1TR1‐min 35S promoter‐driven snowdrop lectin ( Galanthus nivalis agglutinin, GNA) gene, demonstrated the highest expression levels of GNA and lowest BPH survival. Our work identified a BPH‐inducible promoter and three positive regions within it. Transgenic rice with GNA driven by OsAOS1 promoter and positive regions exhibited an expected lethal effect on BPH. This study proved the application potential of BPH‐inducible promoter and provided a novel path for the selection of insect‐resistant tools in the future. Abstract : Isolation and identification of Nilaparvata lugens  inducible promoter and three positive regions within it. Transgenic rice with biocide protein gene driven by the promoter and positive regions exhibited an expected lethal effect on N. lugens . The insect‐inducible promoter is a new strategy in cropping cleaner rice.